RANCANGAN BALANCED SCORECARD SEBAGAI ALAT PENGUKURAN KINERJA: STUDI KASUS PADA SEKOLAH MENENGAH - Hassana, Fheirdha Nur; Harahap, Ludwina; Isgiyarta, Jaka (Universitas Trilogi, 2024)
The research aims to translate and map the school’s vision, mission, and goals into strategic objectives, identifying targets and strategic measures as steps in designing the BSC. The performance measurement framework encompasses four perspectives: financial, customer, internal business processes, and learning and growth. Key findings include a financial performance rating of 66.67% for 2020–2021, reflecting good economic, effectiveness, and efficiency ratios. The customer perspective demonstrated high satisfaction with the quality of services, while the internal business process perspective achieved an excellent score of 86% in innovation and after-sales service. Lastly, the learning and growth perspective indicated strong performance through employee satisfaction and system capability. The study contributes a structured BSC-based performance measurement design, providing SMP AB with a comprehensive tool to evaluate and enhance educational quality.Keywords: Keywords: Balanced Scorecard; Educational Institutions; School Performance Measurement.